2020
DOI: 10.3390/ma13040822
|View full text |Cite
|
Sign up to set email alerts
|

Initial Selection of Disc Brake Pads Material based on the Temperature Mode

Abstract: A spatial computational model of a motor vehicle disc brake, based on the system of equations of heat dynamics of friction and wear (HDFW), was developed. The interrelations of temperature-dependent coefficient of friction and coefficient of intensity of wear through the contact temperature and vehicle velocity were taken into account. The solution of the system of equations of HDFW was obtained by the finite element method (FEM) for six different brake pad materials associated with the cast-iron disc during a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The sintered cermet friction material FMC-11 contains 64% Fe, 15% Cu, 3% SiO 2 , 6% BaSO 4 , 3% asbestos and 9% graphite. Retinax FC-16L is a composite based on phenol-formaldehyde resins and reinforced with brass shavings [ 21 ]. The thermophysical and mechanical properties of materials and friction coefficients of selected pairs at the initial temperature are included in Table 1 .…”
Section: Numerical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The sintered cermet friction material FMC-11 contains 64% Fe, 15% Cu, 3% SiO 2 , 6% BaSO 4 , 3% asbestos and 9% graphite. Retinax FC-16L is a composite based on phenol-formaldehyde resins and reinforced with brass shavings [ 21 ]. The thermophysical and mechanical properties of materials and friction coefficients of selected pairs at the initial temperature are included in Table 1 .…”
Section: Numerical Analysismentioning
confidence: 99%
“…The exact obtained solutions to such problems during single braking cases are in the form of closed engineering formulas and allow for instant assessment of the temperature during braking under light conditions with sufficient accuracy; when the volumetric and the average temperatures of the friction surface do not exceed 100 °C and 200 °C, respectively [ 18 , 19 , 20 ]. Under heavy and medium braking conditions, when the volume temperature reaches values above 250 °C, the friction coefficient and properties of the friction pair materials change significantly due to the influence of temperature; therefore, numerical methods are used [ 21 , 22 ]. An attempt was made to use the exact solutions of linear thermal problems of friction to determine temperature during single braking of a system made of thermally sensitive friction materials [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…(1) development of effective 2D and 3D computational models with the use FEM to determine the temperature of the friction clutch; (2) carrying out a comparative analysis of the temperature fields obtained by means of both models with the same friction work done; (3) investigating the effect of a carbon-containing additive in the structure of the new four friction materials on the temperature mode of the clutch. (4) When developing the computational models of frictional heating of the clutch, the authors used their previous experience, gained earlier in the modeling of the temperature mode of disc brakes [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that instead of straight vanes if the pillar arrangement was made then it is possible to increase the fatigue life of the brakes. Yevtushenko and Grzes [19,20] have studied disc brake using spatial computational model. They studied temperature dependent coefficient of friction by considering contact temperature and vehicle velocity.…”
Section: Introductionmentioning
confidence: 99%